2013
DOI: 10.1002/chem.201303500
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Hydrogenation of 1‐Alkylvinyl Benzoates: A Simple, Nonenzymatic Access to Chiral 2‐Alkanols

Abstract: Going chiral! Highly enantioselective catalytic hydrogenations of enol esters 1 by using a Rh catalyst bearing a P-OP ligand are described (see scheme; NBD=norbornadiene). The catalytic system has a broad scope and allows the preparation of a wide range of chiral esters 2 bearing diverse alkyls or a benzyl group with high enantioselectivities. These esters can easily be converted in highly enantioenriched 2-alkanols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…The most active catalyst of the series, i.e., [RuCl 2 (η 3 :η 3 -C 10 H 16 )(PPh 3 )] (31a), showed also a wide scope allowing the preparation of a large variety of enol esters 32 by selective Markovnikov addition of different carboxylic acids to both aliphatic and aromatic terminal alkynes, as well as to 1,3-enynes (Scheme 19) [68,72,73]. As a general trend, the reactions proceeded faster, and with higher yields, when aliphatic terminal alkynes were employed as substrates.…”
Section: Catalytic Addition Of Carboxylic Acids To Terminal and Intermentioning
confidence: 99%
See 2 more Smart Citations
“…The most active catalyst of the series, i.e., [RuCl 2 (η 3 :η 3 -C 10 H 16 )(PPh 3 )] (31a), showed also a wide scope allowing the preparation of a large variety of enol esters 32 by selective Markovnikov addition of different carboxylic acids to both aliphatic and aromatic terminal alkynes, as well as to 1,3-enynes (Scheme 19) [68,72,73]. As a general trend, the reactions proceeded faster, and with higher yields, when aliphatic terminal alkynes were employed as substrates.…”
Section: Catalytic Addition Of Carboxylic Acids To Terminal and Intermentioning
confidence: 99%
“…Further evidence of the versatility of [RuCl 2 (η 3 :η 3 -C 10 H 16 )(PPh 3 )] (31a) was gained in the reactions of the terminal diynes 33 with benzoic acid. Thus, as shown in Scheme 20, the corresponding enynes 34 or the diesters 35 could be selectively synthesized with 31a just by adjusting the diyne/benzoic acid ratio employed [68,72,73]. Further evidence of the versatility of [RuCl2(η 3 :η 3 -C10H16)(PPh3)] (31a) was gained in the reactions of the terminal diynes 33 with benzoic acid.…”
Section: Catalytic Addition Of Carboxylic Acids To Terminal and Intermentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a highly interesting application of the hydrogenation of enol esters corresponds to the reduction of 1‐alkylvinyl esters, since the corresponding products can easily be converted into 2‐alkanols, which are very difficult to access in highly enantioenriched form through the hydrogenation of methyl alkyl ketones 68. At this regard, Pizzano and co‐workers have shown that catalysts with ligands L8a – L8c are broadly applicable in the hydrogenation of substrates possessing different alkyl substituents under very mild conditions (Scheme ) 69. In addition, products with Ph substituents in the alkyl chain are also obtained with very high enantioselectivity.…”
Section: Recent Applications Of P‐op Ligands In Asymmetric Catalysismentioning
confidence: 99%
“…Enol ester derivatives represent a relevant class of compounds widely used as mild acylating reagents, [1][2][3][4] as monomers for the production of diverse types of polymers and copolymers, [5][6][7][8] and as starting materials in a large variety of reactions, including asymmetric hydrogenation, [9][10][11][12] cycloaddition, [13][14][15][16] cyclization, [17][18][19][20] hydroformylation, [21][22][23] cross-coupling, [24][25][26][27] Michael addition, [28][29][30][31] aldol-type, [32][33][34] Mannich-type 35 and amide bond-forming processes, 36 to name a few. The enol ester motif is also found in a number of natural products with relevant biological properties.…”
Section: Introductionmentioning
confidence: 99%